myTraining portal - Furuc, Restituto M. (University of the Philippines Diliman, 2009)
myTraining portal project aims to implement a better system for managing training activities and skills assessment of technical support engineers for TrendLabs Philippines, the research, development and support center for Trend Micro's anti-malware products and services. The company's PH Corporate QA and Training Team (Training Team) is responsible for training the technical support engineers belonging to the operations team and providing them knowledge and skills to achieve high quality service to its customers. Currently, the training team has challenges in aligning their activities to the needs of the operations team. On the other hand, the latter does not leverage on training team to increase product skillset of the support engineers. The training team holds no formal process of conducting training activities, and incorporating operations team processes. The apparent disconnect between the two teams leads to poor training quality and in turn, lowers customer satisfaction rate in the support cases. In the study, these organizational issues were identified and formalized using systems thinking tools such as Levels of Perspective (LOP) and Vision Deployment Matrix (VDM). As a response to the organizational issues, myTraining portal was conceived to aid in performing activities related to managing training courses and engineers' training level from training course creation to post-training tasks. Some of the features of the portal include permission-based training calendar, training request and registration, attendance and certification recording, performance tracking, training dashboard, reports and views, training surveys, and auto notifications. The features were designed based on the issues identified in the old training processes. A new support training process was documented by the project team and training team which incorporates the portal features. The projects was implemented in accordance to Business Process Project Development Life Cycle (BPLC) of Trend Micro. BPLC serves as a framework in performing project tasks efficiently and facilitating smooth project execution. BPLC is a means to achieve the goal of completing deliverables on time, within specified budget and of desired quality. An online survey was conducted after the initial launched of the system, focusing on the features and functionalities of the portal. The project team also interviewed the training team as well as selected people from the operations team (team leaders and support engineers) with regards to the effectiveness of the portal and the new support process. The project was completed on time and its objectives were met. The issues identified in the old training process were addressed by the functionalities of the portal. Based on the survey and interviews conducted after the system launch, majority of the users agreed that the portal has helped in managing training activities, recording and tracking engineer performance and improving the awareness of trainings activities. As a limitation, the project does not cover other enhancement plans such as training course curriculum improvement, and improving communication and feedback loop between training team and operations team.